CORRELATION OF Hba1c LEVELS WITH PUPILLARY RESPONSE TO APRACLONIDINE 0,5% EYE DROPS IN PATIENTS WITH TYPE 2 DIABETES MELLITUS - Devi Azri Wahyuni; Nafila Mahida Sukmono; Erial Bahar (Fakultas Kedokteran Universitas Sriwijaya, 2020)
Pupillary reflex abnormalities can result from disorders of the innervation or iris structure of the eye. In people with diabetes mellitus, the pupil size becomes smaller than normal due to neuropathy in innocent sympathetic innervation of the pupil. This neuropathy is associated as a manifestation of uncontrolled diabetes complications. Pupillary response is associated as a general indication of autonomic neuropathy disorders in diabetes mellitus patients. Apraclonidine as an ophthalmic sympathomimetic agent can cause mydriasis, which is likely to identify pupillary sympathetic denervation in type 2 diabetes mellitus patients. This study aimed to find out the correlation between HbA1c levels and pupillary response to 0.5% Apraclonidine eye drops in diabetes mellitus type 2 patients at Mohammad Hoesin Hospital Palembang. Observational research with a correlation test design to investigate the correlation of HbA1c levels with pupillary response to apraclonidine 0.5% eye drops in patients with type 2 diabetes mellitus has been conducted from March to May 2019. The study sample met the inclusion and exclusion criteria of 31 diabetics mellitus type 2 with HbA1c level> 6.5% in the Eye clinic at the Mohammad Hoesin Palembang hospital. In this study 31 patients with type 2 diabetes mellitus with HbA1c levels >6.5 mg% were obtained. The average HbA1c level was 9.5 ± 1.4 mg%, which ranged from 7.6 - 12.6 mg%. The glycemic status of the patients in this study were all (100.0%) in an uncontrolled condition (HbA1c> 7.5 mg%). The estimated duration of diabetes mellitus is 2.7 ± 1.8 years, with a minimum value of 1 year and the largest being 8 years. The average change in pupillary diameter before - after dropping 0.5% apraclonidine was 1.16 ± 1.06 mm, ranging from 0 - 4 mm. There were 9 (29.0%) eyes that did not show any changes. Significant enlargement of pupillary size after dropping 0.5% apraclonidine (p = 0,000). This change in pupil size correlated with the estimated duration of diabetes mellitus (r = 0.436, p = 0.014) and HbA1c levels (r = 0.492, p = 0.005). Pupil size after using 0.5% apraclonidine has a distribution value of 4 (3-6) mm can be interpreted that there are subjects who have no change, but there are patients who have pupils dilated to 6 mm.